Pelatihan Media Digital Interaktif Blooket Integrasi AI dalam Pembelajaran Modern di SD - Yessi Yunitasari; Inung Diah Kurniawati; Yoga Prisma Yuda; Pratiwi Susanti (CV. ITTC INDONESIA, 2026)
In the era of 21st-century education, digital literacy has emerged as a crucial competency that extends beyond basic technical skills to encompass critical thinking, information evaluation, and digital ethics. However, educators face significant challenges in maintaining student engagement amidst high levels of digital distraction. This article describes the implementation of training designed to strengthen digital literacy in instruction through the integration of AI and the interactive platform Blooket. The training aimed to enhance educators' competence in utilizing digital technology effectively, creatively, and pedagogically. A participatory training approach was employed, combining lectures, demonstrations, hands-on practice, and post-training evaluation. The results indicate an improvement in participants' understanding of digital literacy, their ability to integrate AI into instruction, and their skills in using Blooket as an interactive and engaging tool for learning assessment. Furthermore, participants demonstrated increased motivation to develop technology-based instruction. Thus, the training proved effective in enhancing teachers' digital competencies and fostering instructional innovation in the era of digital transformation